2015
DOI: 10.1037/xan0000052
|View full text |Cite
|
Sign up to set email alerts
|

Stress increases cue-triggered “wanting” for sweet reward in humans.

Abstract: Stress can increase reward pursuits: This has traditionally been seen as an attempt to relieve negative affect through the hedonic properties of a reward. However, reward pursuit is not always proportional to the pleasure experienced, because reward processing involves distinct components, including the motivation to obtain a reward (i.e., wanting) and the hedonic pleasure during the reward consumption (i.e., liking). Research conducted on rodents demonstrates that stress might directly amplify the cue-trigger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
102
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(111 citation statements)
references
References 27 publications
7
102
2
Order By: Relevance
“…1A and B). These effects have been recently replicated in humans (Pool, Brosch et al, 2014a) through behavioral stress induction. In this experiment, a stressful state was induced by asking participants to keep their hand in ice-cold water while being observed and videotaped.…”
Section: Pavlovian System and Motivationmentioning
confidence: 86%
See 1 more Smart Citation
“…1A and B). These effects have been recently replicated in humans (Pool, Brosch et al, 2014a) through behavioral stress induction. In this experiment, a stressful state was induced by asking participants to keep their hand in ice-cold water while being observed and videotaped.…”
Section: Pavlovian System and Motivationmentioning
confidence: 86%
“…Classic studies show that the perception of a stimulus (e.g., a sound) that has previously been associated with a rewarding outcome (e.g., sucrose) increases the amount of energy invested in the instrumental action (e.g., pressing a lever to obtain sucrose; for reviews, see Bindra, 1974;Bolles, 1972;Toates, 1998). This phenomenon is known as Pavlovian-instrumental transfer and its existence has been largely replicated in animals (e.g., Corbit & Balleine, 2005Wassum, Ostlund, Balleine, & Maidment, 2011;Wyvell & Berridge, 2001) and in humans (e.g., Allman et al, 2010;Bray, Rangel, Shimojo, Balleine, & O'Doherty, 2008;Pool, Brosch, Delplanque, & Sander, 2014a;Prevost et al, 2012;Talmi et al, 2008;Trick, Hogarth, & Duka, 2011).…”
Section: Pavlovian System and Motivationmentioning
confidence: 95%
“…This number of studies confirms that among researchers investigating human reward, there is a great deal of interest in testing predictions of the incentive salience hypothesis. Basic research tested whether results from animal studies could be replicated in human studies by using brain imagining techniques (e.g., fMRI, PET; Born et al, 2011;Leyton et al, 2002), dopaminergic manipulations (e.g., dopaminiergic drug administration; Leyton et al, 2002Leyton et al, , 2005 or methods that are as similar as possible to the original animal studies (e.g., Pool et al, 2015b). More applied research explored whether the potential independence of wanting and liking might represent a mechanism underlying a variety of problematic behaviors such as excessive food consumption (e.g., Lemmens et al, 2011c), substance addiction (e.g., Goldstein et al, 2010) or behavioral addictions (e.g., gambling, excessive video game playing; Thalemann et al, 2007;Wölfling et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…amygdala, nucleus accumbens) increases after the perception of the cue and decreases during reward receipt (Kumar et al, 2014). This translates behaviorally into an increase in cue-triggered wanting without a parallel increase in liking (Pecina et al, 2006;Pool et al, 2015b).…”
Section: Differentiating Expected Pleasantness From Affective Relevanmentioning
confidence: 99%
“…For instance, Pool et al [128] have recently shown that stress affects one of the components of reward but not others. More specifically, stress increases "wanting" (i.e., the motivation to obtain a reward), but not "liking" (i.e., the hedonic pleasure during the reward consumption) for a sweet reward.…”
Section: Amygdala and Unhealthy Food Intake In Acute And Chronic Stressmentioning
confidence: 99%